NDUFC1 Is Upregulated in Gastric Cancer and Regulates Cell Proliferation, Apoptosis, Cycle and Migration - Xu, Liang; Chen, Xiuxiu; Jiang, Hongtao; Xu, Jian; Wang, Lixia; Sun, Yuemin (Frontiers in Oncology, 2021)
Gastric cancer is one of the most common primary tumors of the digestive system. NADH: ubiquinone oxidoreductase subunit C1 (NDUFC1), which is an accessory subunit of the NADH dehydrogenase (complex I), is responsible for the transportation of electrons from NADH to the respiratory chain essential for the oxidative phosphorylation. However, little is known about the roles of NDUFC1 in carcinogenesis. In this study, NDUFC1 protein level in NSCLC tissues was tested by immunohistochemistry (IHC) staining. NDUFC1 mRNA level in gastric cancer cell lines was determined by qRT-PCR. MGC-803 and SGC-7901 cells were transfected with shNDUFC1 lentivirus designed to silence NDUFC1. MTT assay, CCK8 assay, wound healing assay and transwell migration assay were conducted. Cell cycle and apoptosis were detected by flow cytometry. In vivo experiments were performed using nude mice. The results indicated that overexpressed NDUFC1 in gastric cancer was related to more serious tumor infiltrates, a higher risk of lymphatic metastasis, a higher proportion of positive lymph nodes, and a more advanced tumor stage. Compared with shCtrl groups, MGC-803 and SGC-7901 of shNDUFC1 groups had lower abilities of proliferation and migration, higher levels of apoptosis. NDUFC1 knockdown also inhibited SGC-7901 cell growth in vivo and suppressed Ki67 expression in xenograft tumors. More importantly, we found that NDUFC1 downregulation made the levels of P-Akt, P-mTOR, CCND1, CDK6, PIK3CA, Bcl-2, Survivin and XIAP decreased, and that PI3K/AKT signaling pathway agonist SC79 rescued the inhibitory effects on cell proliferation and migration, reversed the promoted effects on cell apoptosis caused by NDUFC1 knockdown. More importantly, compared with NDUFC1 knockdown group, the expression of P-Akt, Bcl-2, Survivin and XIAP was raised in shNDUFC1+SC79 group. Thus, our suspicion was that NDUFC1 exacerbates NSCLC progression via PI3K/Akt pathway. Taken together, our study indicated that targeting NDUFC1 could open innovative perspectives for new multi-targeting approaches in the treatment of gastric cancer.